A novel biodegradable film based on κ-carrageenan activated with olive leaves extract - Martiny, Thamiris R.; Pacheco, Bruna S.; Pereira, Claudio M. P.; Mansilla Muñoz, Andres Omar; Astorga España, Maria Soledad; Dotto, Guilherme L.; Moraes, Caroline C.; Rosa, Gabriela S. (My University, 2020)
This research focused on the development of carrageenan based biodegradable films incorporated with olive leaves extract (OLE). OLE microbial inhibition and its total phenolics (TP) were evaluated. Carrageenan films were produced by casting technique and were characterized by thickness, water vapor permeability (WVP), color, mechanical properties, and infrared spectroscopy. In order to apply as lamb meat packaging, the antimicrobial effect of the films was investigated. Results showed that OLE inhibited E. coli growth and presented excellent TP (41.40 mg(GAE)/g). Thicknesses of the film with OLE (CAR-OLE) were approximately 28% higher than film without OLE. Addition of OLE reduced the WVP by approximately 54%. CAR-OLE was less resistant to breakage and more flexible showing darker color. FTIR showed interaction of carrageenan with OLE. Results revealed that CAR-OLE promoted 167-fold reduction in initial count of aerobic mesophiles indicating shelf-life extension of lamb meat and promising use as antimicrobial food packaging.
Keywords: active packaging; antimicrobial packaging; biopolymer; food packaging; lamb meat